Dividend payout ratio follows a Tweedie distribution: International evidence - Victor Dragotă; Daniel Traian Pele; Hanaan Yaseen (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
Dividend policy is still a largely discussed issue in corporate finance literature. One of the main indicators used in analysing the dividend policy is the dividend payout ratio. Using a database consisting of 12,085 companies operating in 73 countries, for the period 2008-2014, the authors found that the dividend payout ratio follows a Tweedie distribution, and not a normal one. This distribution is stable over time for the entire analysed period. In addition, it describes the case of almost all the countries included in the sample. Thus, a better estimation of the probability that dividend payout ratio is lower or higher than a benchmark can be provided. Also, an analysis of dividend policy, distinctly considering payer versus non-payer companies, can offer additional important information for both practitioners and academics.
http://dx.doi.org/10.7910/DVN/MZMINU
Keywords: G35; C01; C51; C55; 330; dividend policy; dividend payout ratio; Tweedie distribution